Penerapan Metode Weight Product Pemilihan Guru Terbaik Di SMK Penerbangan Sidoarjo - Azizissani, Rizqi (Journal of Electrical, Electronic, Mechanical, Informatic and Social Applied Science, 2023)
Teachers in the school environment have an important role and many individuals are interested in becoming teachers, although not all of them meet the specified criteria. This research aims to develop a system that can assess the level of suitability of the best teachers in private schools by applying the Weight Product method. This method involves steps such as identifying criteria, calculating weights, calculating vector S, calculating vector V, and ranking. The result of this research is a decision support system that is able to determine the best teachers who are worthy of being role models in a private school environment. In this way, schools can choose teachers who are most competent in managing and guiding students, improving the quality of education, and creating a better learning environment. Guru di lingkungan sekolah mempunyai peranan yang penting dan banyak individu yang berminat menjadi guru, walaupun tidak semuanya memenuhi kriteria yang ditentukan. Penelitian ini bertujuan untuk mengembangkan sistem yang dapat menilai tingkat kesesuaian guru terbaik di sekolah swasta dengan menerapkan metode Weight Product. Metode ini melibatkan langkah-langkah seperti identifikasi kriteria, penghitungan bobot, penghitungan vektor S, penghitungan vektor V, dan pemeringkatan. Hasil dari penelitian ini adalah sebuah sistem pendukung keputusan yang mampu menentukan guru-guru terbaik yang layak menjadi teladan di lingkungan sekolah swasta. Dengan cara ini, sekolah dapat memilih guru yang paling berkompeten dalam mengelola dan membimbing siswa, meningkatkan mutu pendidikan, dan menciptakan lingkungan belajar yang lebih baik.